2007
DOI: 10.1002/arch.20208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural characterization of a trypsin highly expressed in larval stage of Zabrotes subfasciatus

Abstract: The Mexican bean weevil, Zabrotes subfasciatus, feeds on several seeds such as Vigna unguiculata, Phaseolus vulgaris, and Pisum sativum, causing severe crop losses. This ability to obtain essential compounds from different diets could possibly be explained due to a wide variability of digestive proteinases present in the weevil's midgut. These may improve digestion of many different dietary proteins. Coleopteran serine-like proteinases have not been thoroughly characterized at the molecular level. In this repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…FJ917598) encoding a 259-amino-acid protein (Figure 1). These characteristics were consistent with previous reports (Klein et al, 1996;Magalhaes et al, 2007;Rudenskaya et al, 2004) for other trypsins. Speaking with strict definition, the sequence cloned in this study was a trypsinogen gene.…”
Section: Cloning Of the Full-length Cdna And Genomic Dna Of Sptrypsupporting
confidence: 94%
“…FJ917598) encoding a 259-amino-acid protein (Figure 1). These characteristics were consistent with previous reports (Klein et al, 1996;Magalhaes et al, 2007;Rudenskaya et al, 2004) for other trypsins. Speaking with strict definition, the sequence cloned in this study was a trypsinogen gene.…”
Section: Cloning Of the Full-length Cdna And Genomic Dna Of Sptrypsupporting
confidence: 94%
“…; Magalhães et al . ). Thus, both the dominance of trypsin‐like activity and the low sensitivity of chymotrypsin‐like activity to Kunitz‐type PIs appear to be common features of beetles.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, in a recent study, trypsin and chymotrypsin were identified as the most active proteases in P. truncatus, and trypsin-like activity was more sensitive than chymotrypsin to plant PIs extracted from the seeds of tepary bean (Phaseolus acutifolius), soybean (G. max, both: Fabaceae) and chan (Hyptis suaveolens; Lamiaceae) (Castro-Guill en et al 2012). Similarly, chymotrypsin-like activities in Z. subfasciatus were not inhibited by natural PIs from soybean and common bean (Phaseolus vulgaris) (Silva et al 2001;Magalhães et al 2007). Thus, both the dominance of trypsin-like activity and the low sensitivity of chymotrypsin-like activity to Kunitz-type PIs appear to be common features of beetles.…”
Section: Discussionmentioning
confidence: 97%
“…The Mexican bean beetle (MBB), Zabrotes subfasciatus (Bohemann) (Coleoptera: Chrysomelidae: Bruchinae), is a key pest of stored beans, attacking beans belong to the genera Phaseolus, Vicia and Vigna (Hill, 2002). In Brazil, MBB also infests other types of beans such as Vicia and Vigna and other legumes such as peas (Pisum sativum L. Fabaceae) probably because of the presence of a great number of digestive proteinases that exist in the insect's midgut (Magalhães et al, 2007). Infested seeds lose mass, quality and nutritional value, the latter two due to the presence of frass, eggs and dead insects in the product.…”
Section: Introductionmentioning
confidence: 99%